A novel, high-sensitivity and drug-tolerant sandwich immunoassay for the quantitative measurement of circulating proteins. (February 2012) - Sloan, John H; Ackermann, Bradley L; Carpenter, John W; Nguyen, Huy T; Stopa, Kimberly; Siegel, Robert W; Konrad, Robert J
Background: Accurate measurement of a total protein target (free plus bound) is essential to optimize dose selection for monoclonal antibody drugs. Herein, we describe a novel sandwich immunoassay format in which the biotherapeutic antibody itself serves as the primary detection antibody. A signal is then generated through the addition of a labeled secondary antibody that recognizes the biotherapeutic antibody. The secondary antibody is conjugated with ruthenium to facilitate electrochemiluminescent analysis.Results: Data are presented from the analysis of two protein biomarkers having disparate size and structure; a 4.5 kDa peptide and a 60 kDa protein. In both cases, validated, highly specific assays were developed and shown to be tolerant to elevated levels of the therapeutic monoclonal antibody in question.Conclusion: Our novel format allows drug-tolerant measurement of soluble protein biomarkers targeted by monoclonal antibodies when only two independent epitopes for antibody binding are available and one is recognized by the therapeutic antibody.